A Comparative content analysis of the Philippine Star and the Philippine Daily Inquirer on the controversy at the SBMA from June 1 to August 31, 1998 - Beligan, Enthrem Z.; Liquigan, Boots Casafrancisco; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
In an effort to document, at least in part, the controversial issue at the Subic Bay Metropolitan Authority (SBMA), this content analysis was undertaken to determine the slant or position of the Philippine Daily Inquirer and the Philippine Star on the said issue. A total number 164 news articles from June 1 to August 31, 1998 were gathered and analyzed. Of the total sample population, Inquirer published 94 news articles (57%) while Star had a total of 70 articles equivalent to 43%. Results revealed that Inquirer gave more prominence to the SBMA issue in terms of frequency, number of paragraphs, and the average number of paragraphs allotted for each news article. Based on page location, section, and degree of attention however, more emphasis was given by the Philippine Star. Most of the news articles of both newspapers were found to be politically inclined. A few were classified under the economic aspect. Findings also show that most of the news articles published by the Philippine Star were favorable to the government which was pro-Payumo, while that of Inquirer were mostly neutrally toned. On the other hand, the often-used approach or slant by both broadsheets was imbalanced and active. Imbalanced and passive was found to have the lowest frequency for both broadsheets. As much as Inquirer tried to maintain a neutral tendency in the presentation of its news articles, findings revealed that the publication was more aware and supportive of the issue on th SBMA that the Philippine Star.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Subic Bay Metropolitan Authority (SBMA) -- Philippines -- Newspaper reporting; Philippine Daily Inquirer -- Philippines -- Newspaper sections; Philippine Star -- Philippines -- Newspaper sections